An investigation into mathematics education students’ logical reasoning in real analysis - Edi Purwanto; Nita Fatma Fauziah (UNION : Jurnal Ilmiah Pendidikan Matematika, 2025)
This study is grounded in the urgency of strengthening logical reasoning in advanced mathematics, particularly in Real Analysis, where students are required to transition from procedural thinking to formal deductive proof. However, many mathematics education students still experience difficulties in constructing valid arguments, understanding formal definitions, and managing logical structures in proof-based contexts.This study explores mathematics education students’ logical reasoning after completing the Real Analysis course, a core subject emphasizing deductive proof and abstraction. The study employed a qualitative approach with a descriptive method. Students’ logical thinking abilities were assessed through problem-solving test scores aligned with established indicators of mathematical logical reasoning. Data analysis consisted of reduction, presentation, coding, conclusion drawing, and verification. The findings reveal that students’ logical thinking ability in the Real Analysis course falls within the moderate category. The highest achievement was found in indicator 2, namely the ability to draw conclusions or make predictions based on probability, which reached the high category. Conversely, the lowest performance was observed in indicator 3, drawing conclusions or making predictions based on the correlation between two variables, categorized as low. The findings provide insight for improving reasoning-oriented instruction in Real Analysis. This study contributes to mathematics education by providing an empirical and indicator-based profile of students’ logical reasoning in advanced mathematics, offering a foundation for designing targeted instructional strategies to enhance proof-oriented learning in Real Analysis courses.